Economic Social Cultural Analysis of Sports Coaching Program in East Nusa Tenggara Province - Ary Moelyadi (Kazimierz Wielki University, 2020)
This study aims to analyze the economic social cultural in sports coaching programs in East Nusa Tenggara Province. This study uses a naturalistic phenomenological approach with qualitative method. The technique used for data collection is observation and in-depth interviews with key informants and is accompanied by documentation. Based on the results of this study concluded that (1) The potential of environmental and socio-cultural resources is a major factor in development of sports in East Nusa Tenggara Province; (2) Cultural values in East Nusa Tenggara Province are determining the pattern of sports development and sports, one of which is the culture of discipline developed by kempo sport and also the existence of traditional games such as "pikul air"( water shoulder) in childhood, because there are movements in the fast way; (3) The basic needs of athletes in achieving sports achievements to show their identity as East Nusa Tenggara society are the clarity of the target to be achieved so that not only the branches of the kempo sport and boxing are superior but other sports such as sepak takraw and silat can develop their achievements; (4) Martial arts and individual sports are the super priority in East Nusa Tenggara is kempo sport and boxing. Synergy is needed between sports stakeholders and all parties sitting together to formulate appropriate policies and programs. It is important for the government to be able to explore more other sports that can be superior in East Nusa Tenggara.